Intrahepatic cholangiocarcinoma with bile duct tumour thrombus: a case for complete resection - Kamal, Harshit; Singh, Malika; Riyaz, Mohammad; Mudadla, Rohith; Devakumar, Murugesan S.; Satyanesan, Jeswanth (International Surgery Journal, 2022)
Intrahepatic cholangiocarcinoma (ICC), which is ordinarily a very invasive tumor and often takes a rapid and fatal course, sometimes shows macroscopic intra bile duct extension. We present a case of a 45-year-old Indian gentleman who presented with jaundice. Further evaluation with contrast enhanced computed tomography (CECT) and magnetic resonance imaging (MRI) abdomen revealed mass lesion in segment 4 of liver with extension into the bile duct. A formal left hepatectomy with gall bladder and bile duct tumour thrombus extraction with bile duct excision followed by a Roux-en-Y hepaticojejunostomy was performed. Intra bile duct growth of ICC may reflect indolent biological behavior and thus warrants an aggressive surgical approach, which appears to give a good prognosis.